Artificial intelligence lives among us: dialogues on its social and regulatory impacts - Carvalho, Juliano Maurício de [UNESP] (OSF (Open Science Framework / Center for Open Science), 2026)
This study examines the social and regulatory implications of artificial intelligence (AI), focusing on its rapid popularization and disruptive potential. It adopts a qualitative, exploratory approach grounded in bibliographic and documentary research, with descriptive-analytical examination of international and national reports and regulatory frameworks. The paper contextualizes AI as a global debate topic present in multilateral organizations, educational environments, and corporate strategies, highlighting tensions between technological progress and social structures. It discusses the impact of generative AI tools, such as ChatGPT, on professional markets, education, and governance. International regulatory initiatives are analyzed, including the European Union’s Artificial Intelligence Act, the United Kingdom’s National AI Strategy, and U.S. actions to consolidate leadership in research and development. In Brazil, the study reviews the legislative trajectory culminating in Bill No. 2,338/2023, which proposes principles, rights, risk classification, and governance mechanisms for AI systems. Ethical dimensions—such as transparency, accountability, bias mitigation, and fairness—are addressed, along with challenges in translating normative concepts into algorithmic frameworks. The paper also explores controversies surrounding copyright and remuneration for creators whose works train AI models, as well as risks related to disinformation, deepfakes, and national security. It concludes by advocating adaptive regulation, inclusive governance, and continuous social dialogue in light of emerging issues concerning authorship, authenticity, and equitable labor transitions in the era of generative AI.
A inteligência artificial mora entre nós: diálogos sobre seus impactos sociais e regulatórios
Keywords: Artificial Intelligence; Brazil